1993
DOI: 10.1111/j.1471-4159.1993.tb03183.x
|View full text |Cite
|
Sign up to set email alerts
|

Laminin A, B1, and B2 Chain Gene Expression in Transected and Regenerating Nerves: Regulation by Axonal Signals

Abstract: Laminin A, B1, and B2 chain mRNA levels in degenerating and regenerating mouse sciatic nerves were examined using northern blot analysis. In normal intact nerves, B1 and B2 mRNA steady-state levels were high, but when the nerves were crushed, the steady-state levels of B 1 and B2 mRNA per milligram wet tissue weight of the distal segments of the nerves increased five-to eightfold over that of control levels as the total RNA and 0-actin mRNA levels increased, suggesting that these increases were the consequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 55 publications
3
18
0
2
Order By: Relevance
“…It is interesting to speculate that the continued expression of some laminin chains in the peripheral nerve may be related to the promotion of regeneration in settings of axon injury. In support of this, several studies have demonstrated an increase in laminin expression during axonal regeneration (Liesi, 1985a;Zak et al, 1987;Sanes, 1989;Doyu et al, 1993;LeBeau et al, 1995). Our demonstration of the apparent lack of laminin expression in non-neuronal cells along the optic nerve is consistent with the more restricted growth of retinal ganglion cell axons after optic nerve injury in mammals (Liesi, 1985a).…”
Section: Developmental Regulation Of Laminin Expression In Cells Of Tsupporting
confidence: 81%
“…It is interesting to speculate that the continued expression of some laminin chains in the peripheral nerve may be related to the promotion of regeneration in settings of axon injury. In support of this, several studies have demonstrated an increase in laminin expression during axonal regeneration (Liesi, 1985a;Zak et al, 1987;Sanes, 1989;Doyu et al, 1993;LeBeau et al, 1995). Our demonstration of the apparent lack of laminin expression in non-neuronal cells along the optic nerve is consistent with the more restricted growth of retinal ganglion cell axons after optic nerve injury in mammals (Liesi, 1985a).…”
Section: Developmental Regulation Of Laminin Expression In Cells Of Tsupporting
confidence: 81%
“…Laminins are also upregulated following peripheral nerve injury (Martini, 1994;Wallquist et al, 2002) with an increase in laminin a2, a4, b1, and c1 chains, likely forming laminins-211 and -411 in injured nerves (Siironen et al, 1992;Doyu et al, 1993;Wallquist et al, 2002). Experiments using function-blocking antibodies have highlighted the important role played by a2 laminin in promoting neurite outgrowth on sciatic nerve sections in vitro (Agius and Cochard, 1998).…”
Section: Integrin-ecm Interactions During Regeneration Of the Somatosmentioning
confidence: 96%
“…Numerous studies have demonstrated that laminin not only improves neurite growth but also mediates Schwann cell migration, proliferation, or (re)myelination Condic 2008: Tucker andMearow 2008;Chen et al 2007;Previtali et al 2001). Following peripheral nerve injury, specific laminin subunits are up-regulated by Schwann cells (Wallquist et al 2002;Doyu et al 1993) favoring the formation of laminin-2 (-211, 0 α2ÎČ1Îł1-laminin) and laminin-8 (-411, α4ÎČ1Îł1-laminin). These laminin-substrates provide improved growth support for dissociated adult mouse sensory neurons after addition of NGF (Plantman et al 2008).…”
Section: The Extracellular Matrix Components Laminin and Fibronectinmentioning
confidence: 98%